pHealth 2018: proceedings of the 15th International Conference on Wearable Micro and Nano Technologies for Personalized Health, 12-14 June 2018, Gjøvik, Norway - Blobel, Bernd; Yang, Bian (Studies in health technology and informatics, 2018)
Developing an Android-Based Patient Decision Aid Based on Ottawa Standards for Patients After Kidney Transplant and Its Usability EvaluationEmbedded Sensor Systems for Health -- A Step Towards Personalized Health; Vital Signs and Activity Monitoring; Cuffless Blood Pressure Estimation Using Pulse Transit Time and Photoplethysmogram Intensity Ratio; Quality Index Analysis on Camera-Based R-Peak Identification Considering Movements and Light Illumination; Human Activity Recognition Supported on Indoor Localization: A Systematic Review; pHealth Solutions for Decision Support